Мойдодыр: сказки / К. И. Чуковский - Чуковский Корней Иванович (3 любимых сказки, 2017)
Экземпляры: ДО мл.аб. (2018) / Инвентарный номер: 54933 / Цена: / Авт.знак: Ч-88 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6